The efficacy of oxytocin gel in postmenopausal women with vaginal atrophy: an updated systematic review and meta-analysis - Ramadan Abdelmoez Farahat; Hazem Mohamed Salamah; Abdelrahman Mahmoud; Esraa Hamouda; Mahmoud Hashemy; Heba Hamouda; Ali Samir; Imane Chenfouh; Ahmed Marey; Dina M. Awad; Elsayed Farag; Mohamed Abd-Elgawad; et al. (BMC, 2023)
Abstract Background Genitourinary syndrome of menopause (GSM) is a common and disturbing issue in the postmenopausal period. Unlike vasomotor symptoms, it has a progressive trend. Our study aims to evaluate the efficacy and safety of oxytocin gel versus placebo gel in postmenopausal women with GSM. Methods A systematic review and meta-analysis synthesizing randomized controlled trials (RCTs) from Web of Science, SCOPUS, PubMed, and Cochrane Central Register of Controlled Trials databases on January 18, 2023. Keywords such as "oxytocin," "intravaginal," "vaginal," "atrophic," and "atrophy" were used. We used Review Manager (RevMan) version 5.4 in our analysis. We used the risk ratio (RR) for dichotomous outcomes and the mean difference (MD) for continuous outcomes; both were presented with the corresponding 95% confidence interval (CI) and were calculated with the Mantel-Haenszel or inverse variance statistical method. Cochrane's Q test and the I2 statistic were used as measures of statistical inconsistency and heterogeneity. The Cochrane Risk of Bias Tool for RCTs was used for the quality assessment of the included studies. Results Seven studies with 631 patients were included. Regarding the maturation index, there was a statistically insignificant increase in the oxytocin arm (MD = 12.34, 95% CI (-12.52-37.19), P = 0.33). Clinically assessed vaginal atrophy showed a statistically significant reduction in the oxytocin group (RR = 0.32, 95% CI (0.23 − 0.10), P < 0.00001). For dyspareunia, vaginal pH, and histological evaluation of vaginal atrophy, there was a statistically insignificant difference between the two groups (RR = 1.02, 95% CI (0.82-1.27), P = 0.84), (MD = -0.74, 95% CI (-1.58-0.10), P = 0.08), and (MD = -0.38, 95% CI (-0.82-0.06), P = 0.09), respectively. There was no significant difference in the safety profile between the two groups as measured by endometrial thickness (MD = 0.00, 95% CI (-0.23-0.23), P = 0.99). Conclusions Although oxytocin has been proposed as a viable alternative to estrogen in the treatment of GSM, our findings show the opposite. Larger, high-quality RCTs are needed to confirm or refute our results. Trial registration PROSPERO registration number CRD42022334357.